IMPLEMENTATION OF AN INTEGRATED GUIDED INQUIRY LEARNING MODEL FOR GENERIC SCIENCE SKILLS ON ACIDS BASE MATERIAL - Anisa, Indri; Dibyantini, Ratu Evina (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2024)
Abstract: This study aims to determine the effect of prior knowledge evaluation and student worksheets on learning outcomes and to determine the differences in learning outcomes between high prior knowledge and low prior knowledge using the Guided Inquiry learning model integrated with Generic Science Skills on Acid Base material. This study uses a dual paradigm design with two independent variables and one dependent variable. The population in this study were all students of class XI MIPA SMA Negeri 1 Pantai Cermin consisting of 3 classes. The sample in this study was taken using a purposive sampling technique of 1 class, namely class XI MIPA 2 with a total of 34 students who were taught with the Guided Inquiry learning model integrated with Generic Science Skills using learning devices consisting of prior knowledge evaluation, teaching materials, student worksheets and evaluation of learning outcomes. The instruments used in this study were the initial knowledge evaluation test instrument, the learning outcome evaluation test instrument, student worksheets and the non-test instrument used was the student observation sheet. Data were analyzed using multiple linear regression tests and Independent Sample T-Test tests. The results of the data analysis obtained showed that there was a significant influence between the evaluation of prior knowledge and student worksheets on learning outcomes and there was a difference between students with high prior knowledge and students with low prior knowledge. Keywords: Guided Inquiry, Generic Science Skills, Acids Base Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh evaluasi pengetahuan awal dan lembar kerja peserta didik terhadap hasil belajar dan untuk mengetahui perbedaan hasil belajar antara pengetahuan awal yang tinggi dan pengetahuan awal yang rendah dengan menggunakan model pembelajaran Inkuiri Terbimbing terintegrasi Keterampilan Generik Sains pada materi Asam Basa. Penelitian ini menggunakan desain paradigma ganda dengan dua variabel independen dan satu variabel dependen. Populasi dalam penelitian ini adalah seluruh peserta didik kelas XI MIPA SMA Negeri 1 Pantai Cermin yang terdiri dari 3 kelas. Sampel dalam penelitian ini diambil dengan menggunakan teknik purposive sampling sebanyak 1 kelas yaitu kelas XI MIPA 2 dengan jumlah peserta didik 34 orang yang diajarkan dengan model pembelajaran Inkuiri Terbimbing terintegrasi Keterampilan Generik Sains dengan menggunakan perangkat pembelajaran yang terdiri dari evaluasi pengetahuan awal, bahan ajar, lembar kerja peserta didik dan evaluasi hasil belajar. Instrumen yang digunakan dalam penelitian ini adalah instrumen tes evaluasi pengetahuan awal, instrumen tes evaluasi hasil belajar, lembar kerja peserta didik dan instrumen non tes yang digunakan adalah lembar observasi peserta didik. Data dianalisis dengan menggunakan uji regresi linear ganda dan uji Independent Sample T-Test. Hasil analisis data yang diperoleh menunjukkan bahwa ada pengaruh yang signifikan antara evaluasi pengetahuan awal dan lembar kerja peserta didik terhadap hasil belajar dan ada perbedaan antara peserta didik yang pengetahuan awal tinggi dengan peserta didik yang pengetahuan awal rendah. Kata Kunci: Inkuiri Terbimbing, Keterampilan Generik Sains, Asam Basa